2020
DOI: 10.1007/s41347-020-00181-4
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Intervention with Technology for E-Weight Loss Study (BITES): Incorporating Energy Balance Models and the Bite Counter into an Online Behavioral Weight Loss Program

Abstract: This study evaluated feasibility and acceptability of adding energy balance modeling displayed on weight graphs combined with a wrist-worn bite counting sensor against a traditional online behavioral weight loss program. Adults with a BMI of 27–45 kg/m2 (83.3% women) were randomized to receive a 12-week online behavioral weight loss program with 12 weeks of continued contact (n = 9; base program), the base program plus a graph of their actual and predicted weight change based on individualized physiological pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, measurements that are obtained from accelerometers are also objective, but can be extremely noisy and are not able to estimate physical activity expenditure well in comparison to gold standard methods [27]. However, the largest source of measurement in nutrition research, self-reported energy intake, is not objective and sometimes not reliable without triangulating with other methods [28] for deriving scientific conclusions [29][30][31].…”
Section: Measurement Errormentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, measurements that are obtained from accelerometers are also objective, but can be extremely noisy and are not able to estimate physical activity expenditure well in comparison to gold standard methods [27]. However, the largest source of measurement in nutrition research, self-reported energy intake, is not objective and sometimes not reliable without triangulating with other methods [28] for deriving scientific conclusions [29][30][31].…”
Section: Measurement Errormentioning
confidence: 99%
“…This does not mean that self-reported dietary intake data is not valuable during interventions. There are examples of self-reported dietary intake data being used in tandem with other tools such as energy intake wearables [44,45] and mathematical models that predict weight loss to guide intake [46] improving dietary adherence even more than any of the dietary assessment methods used alone [28]. The danger of using data like selfreported dietary intake as true intake to train AI/ML models is that the models will identify patterns that are artifacts of error from the input data which will then be used to make erroneous predictions that inform decision-making.…”
Section: Measurement Errormentioning
confidence: 99%
“…Technology-based interventions for weight loss have shown promise in the short term [ 15 , 16 ]; however, the potential of computer engineering has not been fully realized when designing weight loss interventions [ 17 ]. It has been argued that new multicomponent (integrated) electronic platforms integrating education with individually tailored weight loss programs, including the promotion of autonomous motivation, self-efficacy, self-regulation, and positive body image, may present a way forward for wide-scale weight loss solutions and obesity management [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%